Anew Chinese chestnut cultivar Yanli 3 - ZHANG Xinfang; FAN Liying; ZHANG Shuhang; LI Ying; GUO Yan; LIU Jinyu; WANG Guangpeng (Guoshu xuebao)
Yanli 3 is a new high-yield chestnut cultivar selected from the natural seedling chestnut trees in Jiangjunmu town, Xindu district of Xingtai city (former Xingtai county). It was selected by Changli Institute of Pomology, Hebei Academy of Agriculture and Forestry Sciences. We found the superior individual plant during the investigation of chestnut resources in 2001. The mother tree was 60 years old and had the characteristics of high quality, high yield and good resistance to red mites. The scions from the mother tree were collected and introduced into the variety breeding nursery of our institute for systematic evaluation on the main agronomic traits in 2004. After regional adaptability testing at three sites of Hebei Province (including Kuancheng county, Xinglong county and Qianxi county) from 2008 to 2022, it was finally selected and has obtained the certificate of new plant cultivar by National Forestry and Grassland Administration in 2023. The tree is high and the shape is open, mostly in a center-open state. The branch color is greyish-brown, and the size and density of lenticel is intermediate. The leaf color is deep green and leaf shape is ellipse with lobate serration, and gradually acute apex. The length of catkin is about 20.62 cm, and the numbers of catkin on each biennial bearing branch is 13.4. The bur shape is ellipse and cruciform-cracked. The spine bundle length is 1.7 cm, with intermediate angle and large density. Each bur contains about 2.72 nuts. The nut color is reddish-brown, with excellent luster. The side nut shape is ellipse and the apex of nut is flat. The pubescence distribution of nut is around apex, and the density of pubescence is low. The stripes of nut are not obvious, and the hilum size is small. The kernel is faint yellow, and pellicle removal is easy. The nuts are suitable for frying and processing, and cooked nuts taste sweet, fragrant, and glutinous. The nut average weight is 10.86 g and the rate of nut eatability is 35.45%. The water content is 46.7%, and the soluble sugar, starch and protein content are 20.3%, 47.8%, and 4.94%, respectively. The new cultivar Yanli 3 has high and stable yield with a vigorous nut-bearing ability. It can bear nuts in the 2ndyear, and then enter the high yield period in the 3rd or 4th year after grafting. The average production capacity is about 4030 kg·hm-2. The germination rate of biennial bearing branch buds is 73.8%. The biennial bearing branches account for about 47.1%, and the developing branches account for 21.5%.1-year-old branches are strong and stout, with an average length of 32.68 cm, a diameter of 0.81 cm, and an internode length of 1.36 cm. The average number of bearing shoots on each biennial bearing branch is 3.48, and each biennial bearing branch has an average of 2.62 burs. Yanli 3 has good adaptability and is resistant to barren soil, which is suitable for planting in beaches, hills and mountains, such as the chestnut cultivation area of Hebei Province and similar areas. According to “Descriptors and Data Standard for Chestnut”, the resistance of Yanli 3 to red mites is stronger than that of the control variety Yanshanduanzhi. The planting space between plants and rows are 4 m×4 m when the orchard is built. The tree shape of Yanli 3 is suitable for training natural open center system or two-layer small canopy sparse shape. Young trees can achieve early fruiting and high yield by pulling down branches and carving buds, because the new branches grow vigorously. The rotational and renewal pruning technology can be used in mature trees to achieve stable yield every year.